2012
DOI: 10.1117/12.924794
|View full text |Cite
|
Sign up to set email alerts
|

MOSFIRE, the multi-object spectrometer for infra-red exploration at the Keck Observatory

Abstract: This paper describes the as-built performance of MOSFIRE, the multi-object spectrometer and imager for the Cassegrain focus of the 10-m Keck 1 telescope. MOSFIRE provides near-infrared (0.97 to 2.41 m) multi-object spectroscopy over a 6.1' x 6.1' field of view with a resolving power of R~3,500 for a 0.7" (0.508 mm) slit (2.9 pixels in the dispersion direction), or imaging over a field of view of ~6.9' diameter with ~0.18" per pixel sampling. A single diffraction grating can be set at two fixed angles, and ord… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
58
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 288 publications
(59 citation statements)
references
References 3 publications
(3 reference statements)
1
58
0
Order By: Relevance
“…Near-infrared spectroscopic observations of Abell 1703 were carried out with MOSFIRE (McLean et al 2010(McLean et al , 2012 on the Keck-I Telescope on April 11, 2014 UT. The spectroscopic observations were taken using the YJ grating with the J-band filter, which has a resolution of R=3318 and covers a wavelength range of λ=1.15-1.35µm.…”
Section: Keck/mosfire Observationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Near-infrared spectroscopic observations of Abell 1703 were carried out with MOSFIRE (McLean et al 2010(McLean et al , 2012 on the Keck-I Telescope on April 11, 2014 UT. The spectroscopic observations were taken using the YJ grating with the J-band filter, which has a resolution of R=3318 and covers a wavelength range of λ=1.15-1.35µm.…”
Section: Keck/mosfire Observationsmentioning
confidence: 99%
“…Recently Stark et al (2014a) reported tentative CIII] detections in two galaxies with previously confirmed redshifts (z = 6.029 and z = 7.213) from Lyα. Here we build on this progress with an exploration of the strength of high ionization emission features (CIVλλ1548,1551 and He IIλ1640) in a small sample of z 7 UV-selected galaxies using the MOSFIRE (McLean et al 2012) spectrograph on the Keck I tele- scope. We report the detection of strong nebular CIVλ1548 emission in the spectrum of A1703-zd6, a spectroscopically confirmed galaxy at z = 7.045.…”
Section: Introductionmentioning
confidence: 99%
“…The parent sample for this work consists of 315 galaxies in the redshift range 1.95 z 2.65 for which measurements (or upper McLean et al 2010McLean et al , 2012 on the Keck I telescope. An earlier version of this parent sample, with 219 galaxies, was described in detail by Steidel et al (2014), and we refer the reader to that paper for details of the MOSFIRE observations and data reduction.…”
Section: Data and Sample Selectionmentioning
confidence: 99%
“…This is only a factor of ∼ 2 larger than FIRE on Magellan, and it is considerably smaller than many multi-object cryogenic spectrographs on 6-10 meter telescopes today. 31,32 Since SuperFIRE is a single-object spectrograph, such a comparison does not imply that these instruments address identical science. It simply illustrates that fabrication, installation, and telemetry for dewars of this size are within current capabilities.…”
Section: Mechanical and Thermal Designmentioning
confidence: 99%